2016
DOI: 10.1371/journal.pone.0154750
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Demographics and Social Life Events of Asian (Elephas maximus) and African Elephants (Loxodonta africana) in North American Zoos

Abstract: This study quantified social life events hypothesized to affect the welfare of zoo African and Asian elephants, focusing on animals that were part of a large multi-disciplinary, multi-institutional elephant welfare study in North America. Age was calculated based on recorded birth dates and an age-based account of life event data for each elephant was compiled. These event histories included facility transfers, births and deaths of offspring, and births and deaths of non-offspring herd mates. Each event was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 60 publications
0
48
0
Order By: Relevance
“…A similar situation has been reported for Association of Zoos & Aquariums (AZA) accredited zoos in North America. In 2012, only 29 of 68 (43%) zoos with elephants housed a bull and only 11 of those 29 zoos had more than one bull, meaning only 16% of those bulls could interact with other bulls (Prado-Oviedo et al, 2016).…”
Section: Social Circumstances Of Bull Elephants In North American Andmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar situation has been reported for Association of Zoos & Aquariums (AZA) accredited zoos in North America. In 2012, only 29 of 68 (43%) zoos with elephants housed a bull and only 11 of those 29 zoos had more than one bull, meaning only 16% of those bulls could interact with other bulls (Prado-Oviedo et al, 2016).…”
Section: Social Circumstances Of Bull Elephants In North American Andmentioning
confidence: 99%
“…Adult bulls (those older than 25 years) have previously been considered solitary; therefore, zoos and logging camps have only given bulls access to the females for mating (Hartley, 2016). It is now being recognized that adult bulls are highly sociable, and that social interactions have important roles in physiological and behavioural functions, and influence social development in the herd (Veasey, 2006;Prado-Oviedo et al, 2016). Wood (2017) found that adult bulls spent 50Á3% (SD = 19Á9) of their free-choice time in a social situation under 30 m from another individual.…”
Section: Adult Bulls In Zoosmentioning
confidence: 99%
See 1 more Smart Citation
“…Independent variables used for these analyses were chosen based on their significance in alreadypublished multi-variable models for other "gold standard" welfare indicators of the EWP (ovarian 140 cyclicity, stereotypy, body condition, foot and joint health, walking distance and recumbency, and serum cortisol). Full details regarding data collection and variable creation are provided in earlier publications [5][6][7][8][9][10][11][12][13][14][15][16]. Table 1 lists the welfare indicators and descriptions of the independent variables.…”
Section: Independent Variablesmentioning
confidence: 99%
“…A recent 'Elephant Welfare Project (EWP)' took an epidemiological approach to investigating the 60 factors that impact zoo elephant welfare in North America [4]. That study, conducted by a multiinstitutional team of researchers and including 255 elephants at 68 Association of Zoos and Aquariums (AZA) accredited zoos, found that herd social structure, caretaker interactions, and enrichment, and feeding diversity correlated with a variety of welfare outcomes [5][6][7][8][9][10][11][12][13][14][15][16]. In particular, enrichment and social factors were important for reproductive activity and reducing stereotypic behaviors, diversity of Models exhibiting multi-collinearity, as defined by a variance inflation factor of greater than 10 and a 175 Condition Index of greater than 30, were not considered for further analysis.…”
Section: Introductionmentioning
confidence: 99%